EVALUASI KINERJA PELAYANAN PUBLIK PT. PLN WILAYAH RIAU CABANG PEKANBARU - Okta Rukmana (Universitas Riau, 2010)
In order to improve public welfare and enlight nations, electricity power is part of importantproduct for a country. As one of benefecial natural resources which is dominate society, electricity powerwas needed to enrich the society. In case of coverage the need of electricity power fairly and encourage thecapability of a country in supply of electricity power, the license can be given to the government companyto provide electricity power based on the license of electriciy power. In order to increase sustainabledevelopment whis is has environment perspective in electricity sector, it was needed optimal and effecienteffort in using domestic energy resources that has “go green” symbol and effecient technology to guaranteeelectricity supply. The existence of electricity is most influence of the society activity. Because of that, thegovernment has to arrange a policy which is conduct the company in provide electricity power.